On diaspora : Christianity, religion and secularity - Barber, Daniel Colucciello (Eugene, Oregon : Cascade Books, 2011)
"A great deal of attention has been given over the past several years to the question: What is secularism? In On Diaspora, Daniel Barber provides an intervention into this debate by arguing that a theory of secularism cannot be divorced from theories of religion, Christianity, and even being. Accordingly, Barber's argument ranges across matters proper to philosophy, religious studies, cultural studies, theology, and anthropology. It is able to do so in a coherent manner as a result of its overarching concern with the concept of diaspora. It is the concept of diaspora, Barber argues, that allows us to think in genuinely novel ways about the relationship between particularity and universality, and as a consequence about Christianity, religion, and secularism."--
Online resource; title from PDF title page (EBSCO, viewed April 23, 2018).
Includes bibliographical references and index.
Master record variable field(s) change: 050, 072, 082, 650 - OCLC control number change
Keywords: Religion -- Philosophy; Christianity -- Philosophy; Secularism; Particularism (Theology); Universalism; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books